Marseille, les ateliers de potiers du XIIIe s. et le quartier Sainte-Barbe (Ve-XVIIe s.) - Marchesi, Henri; Thiriot, Jacques; Vallauri, Lucy (Documents d'archéologie française, 1997)
In 1991, construction work in the north-east neighbourhood of Marseilles was the opportunity of studying the quarter Sainte-Barbe (5th-17th century). These excavations revealed the remains of an extra muros quarter specialized in the production of pottery during the 13th century. For the first time in France, the production of urban polyvalent workshops over a hundred years could be analyzed (common unglazed ware, glazed cooking ware, painted tin-glazed ware...). The presence of a kiln of Islamic tradition as well as the types of shapes suggest a transfer of the know-how, moving-abouts of the craftsmen and of their productions, and offers a newer view upon the history of techniques and the origins of majolica in Southern France. This book presents a study about kilns with clay rods supporting the vessels around the Mediterranean basin an in the Near-East. It sheds light upon a firing technique which has disappeared in the West. An exceptional documentary source concerning ceramic techniques as well as the history of the City of Marseilles.